2021
DOI: 10.46827/ejsss.v6i6.1141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reward Practices on Employee Job Satisfaction of Kenya Airways, Nairobi City County, Kenya

Abstract: The human resource department plays a vital role in assuring that the employees are satisfied with the job that they do every day. Research has shown that satisfied workers are more productive and committed to their teams. Recently, Kenya Airways have faced numerous challenges resulting from a reduced rate of productivity for their workers and high turnover for its technical staff as a result of an increased level of dissatisfaction ensuing from poor pay, slow career progression, and hiring of expatriates. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…The results are also shared by Abdi (2021) who confirmed that the adopted reward scheme improved employee performance. furthermore, Obonyo and Felistus (2021) noted that rewards led to job satisfaction and highperformance outcomes. These findings imply that an increase in employee performance was recorded in previous financial year.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The results are also shared by Abdi (2021) who confirmed that the adopted reward scheme improved employee performance. furthermore, Obonyo and Felistus (2021) noted that rewards led to job satisfaction and highperformance outcomes. These findings imply that an increase in employee performance was recorded in previous financial year.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…The reward scheme improved employee performance in the commercial banks. Obonyo and Felistus (2021) research was on reward practices and employee job satisfaction at Kenya Airways (KQ) in Nairobi City County, Kenya. The study was informed by high turnover rates and reduced productivity from the dissatisfied KQ workers with complaints of poor pay, hiring expatriates and slow career progression.…”
Section: Rewards and Benefits And Employee Performancementioning
confidence: 99%
See 1 more Smart Citation